1996
DOI: 10.1007/bf01849629
|View full text |Cite
|
Sign up to set email alerts
|

100 000 quinacrine sterilizations

Abstract: 100000 quinacrine nonsurgical female sterilizations have been completed over the past decade involving transcervical insertion of quinacrine (252 mg) as pellets by one, two or three monthly insertions. No deaths have been reported and serious complications are far fewer than for surgical sterilization. Side-effects are mild and transient. Efficacy has improved from 3 pregnancy failures per 100 women at one year to approximately 1 by improved insertion technique and use of adjuvants. Long-term follow-up of earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…Except for bleeding, the incidence of AEs is similar to that reported in previous studies (13,14,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37), that is, they were mild and tolerable and frequently ceased spontaneously. Some of the less common side effects may be masked or enhanced by the disease or the antiretroviral therapy.…”
Section: Figuresupporting
confidence: 85%
See 2 more Smart Citations
“…Except for bleeding, the incidence of AEs is similar to that reported in previous studies (13,14,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37), that is, they were mild and tolerable and frequently ceased spontaneously. Some of the less common side effects may be masked or enhanced by the disease or the antiretroviral therapy.…”
Section: Figuresupporting
confidence: 85%
“…Antiretroviral therapy users and nonusers presented similar AEs after quinacrine sterilization. In regard to safety, AEs and the absence of serious AEs corroborate similar findings in studies involving >175,000 women (unknown HIV serologic findings) who had quinacrine sterilization (10)(11)(12)(13)(14)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). The serial measures of the viral load and CD4þ and CD8þ lymphocytes are important tools to monitor HIV-infected subjects.…”
Section: Figuresupporting
confidence: 76%
See 1 more Smart Citation
“…Topical application of mepacrine is also well known for its nonsurgical female sterilization [14]. In 1950s, a few preliminary studies indicated its usage in asthma, however there were neither any mechanistic evidence for its anti-asthma property nor any further investigations [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The need to make this procedure simple, safe, inexpensive and thereby more acceptable, even in countries with limited surgical facilities, is well recognised. Use of quinacrine pellets has become the most widely adopted method of non-surgical female sterilisation [25]. The FHI has recently decided not to pursue further research on quinacrine, partly because of the relatively high pregnancy rates after quinacrine compared to other contraceptive methods [26].…”
Section: Chemicalmentioning
confidence: 99%